2019
DOI: 10.1021/acs.jpclett.9b00290
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Copper(II)-Doped Cesium Lead Halide Perovskite Quantum Dots with Strong Blue Emission

Abstract: All-inorganic perovskite quantum dots (QDs) have emerged as potentially promising materials for lighting and displays, but their poor thermal stability restricts their practical application. In addition, optical characteristics of the blue-emitting CsPbX3 QDs lag behind their red- and green-emitting counterparts. Herein, we addressed these two issues by doping divalent Cu2+ ions into the perovskite lattice to form CsPb1–x Cu x X3 QDs. Extended X-ray absorption fine structure (EXAFS) measurements reveal that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
248
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(267 citation statements)
references
References 56 publications
9
248
2
2
Order By: Relevance
“…Hence, the stability and PLQY are obviously enhanced by reducing the defect state density and passivating grain boundaries, leading to excellent optoelectronic properties for devices constructed by using the doped perovskites as active layers . Typically, various metal ions, including Bi 3+ , Ni 2+ , Mn 2+ , Cu 2+ , Zn 2+ , Cd 2+ and rare earth ions (eg, Ce 3+ , Er 3+ , Yb 3+ ), have been doped into halide perovskites. In the halide perovskite system, the similar bond energy between doped elements with X and Pb‐X is considered to be one of the key factors that favors impurity incorporation …”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 99%
“…Hence, the stability and PLQY are obviously enhanced by reducing the defect state density and passivating grain boundaries, leading to excellent optoelectronic properties for devices constructed by using the doped perovskites as active layers . Typically, various metal ions, including Bi 3+ , Ni 2+ , Mn 2+ , Cu 2+ , Zn 2+ , Cd 2+ and rare earth ions (eg, Ce 3+ , Er 3+ , Yb 3+ ), have been doped into halide perovskites. In the halide perovskite system, the similar bond energy between doped elements with X and Pb‐X is considered to be one of the key factors that favors impurity incorporation …”
Section: Component Engineering For Blue‐emissive Perovskitesmentioning
confidence: 99%
“…CsPbX 3 nanocrystals have been incorporated into solar cells achieving a record 13.4 % power conversion efficiency (PCE). [15] Other syntheses have expanded this general idea by generating multiple nanocrystal morphologies through ligand mediation [21][22] and reaction tuning, [23] by using different surface ligands for improved quantum yields, [24][25] by increasing surface passivation/repair via salt solutions, [26][27][28][29] as well as by generating other cation/anion compositions through doping [17,[30][31][32][33][34][35] or post-synthetic ion exchange. [12,[19][20] Most reported syntheses of CsPbX 3 follow the work of Protesescu et al who demonstrated a simple, solution-based synthesis for nanocrystals with high luminescence.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54] Park et al observed strong photon antibunching as well as blinking behavior ascribed to charge/discharge events triggered by photoionization in CsPbBr 3 and CsPbI 3 . [56] Both transition metals [35,57] and rare earth metals [34] have been doped into CsPbX 3 , achieving quantum yields greater than 60 % and 170 %, respectively. [55] Pan et al first demonstrated lanthanide doping into CsPbCl 3 , showing improved quantum yield and luminescence bands across the visible and even into the near-IR region.…”
Section: Introductionmentioning
confidence: 99%
“…For light source applications, development of perovskite materials that can sustain for long‐time under high temperature environment is of critical importance as the temperature of the device often exceeds 333 K under continuous operations. [ 111 ] Fan et al found that tetragonal phase MA‐based perovskite microplates evolve to trigonal phase PbI 2 layered crystals after heating up to 358 K, by tracking the process by using transmission electron microscopy. [ 112 ] As shown in Figure a,b, the initial square lattice phase ({400} planes) gradually degraded to a new trigonal phase ({210} planes) after the temperature increased to 358 K for 80 s. After 100 s, only one quarter of the tetragonal phase MAPbI 3 was left.…”
Section: Stability Of Perovskite Materialsmentioning
confidence: 99%